Stress in Academic and Athletic Performance in Collegiate Athletes: A Narrative Review of Sources and Monitoring Strategies - Lopes Dos Santos, Marcel; Uftring, Melissa; Stahl, Cody A.; Lockie, Robert G.; Alvar, Brent; Mann, J. Bryan; Dawes, J. Jay (Frontiers in Sports and Active Living, 2020)
College students are required to manage a variety of stressors related to academic, social and financial commitments. In addition to the burdens facing most college students, collegiate-athletes must devote a substantial amount of time to improving their sporting abilities. The strength and conditioning professional sees the athlete on nearly a daily basis and is able to recognize the changes in performance and behavior an athlete may exhibit as a result of these stressors. As such, the strength and conditioning professional may serve an integral role in the monitoring of these stressors and may be able to alter training programs to improve both performance and wellness. The purpose of this paper is to discuss stressors experienced by collegiate-athletes, developing an early detection system through monitoring techniques that identify the detrimental effects of stress, and discuss appropriate stress management strategies for this population.